Religious Moderation Index in Darul Ikhlas Islamic Boarding School - Ainan Nur (BELIEF: Sociology of Religion Journal, 2023)
This research is motivated by the fact that Indonesia is a multicultural country, including religion, which is a challenge because it can trigger conflict and division if not managed well, the emergence of acts of terrorism in the name of religion and the emergence of movements that want changes to ideology. Islamic boarding schools consistently instill the values of religious moderation in students by using a moderate approach to understanding, far from attitudes of blind fanaticism and liberalism. This research is quantitative research with descriptive methods by collecting data through observation, distributing research questionnaires, interviews, and documentation. The aim of this research is to find out how big the Religious Moderation Index is at the Darul Ikhlas Islamic Boarding School in Dalan Lidang, Panyabungan District, Mandailing Natal Regency. This research measures the religious moderation index at the Darul Ikhlas Dalan Lidang Islamic Boarding School, Panyabungan District, Mandailing Natal Regency, which includes four indicators of the Ministry of Ag's religious moderation, namely, national commitment, tolerance, non-violence and accommodating to local culture. It is found that the Religious Moderation Index at the Darul Ikhlas Dalan Lidang Islamic Boarding School, Panyabungan District, Mandailing Natal Regency is 27.36% in the low category. Caused by a lack of understanding of religious moderation in the Islamic boarding school environment.